Physiological response to sub lethal concentration of nickel on marine and fresh water algae - Manju, M R; Balakrishnan, K P (Indian Journal of Fisheries, 2011)
Effect of nickel at low levels on chlorophycean alga and a diatom was studied. A comparative study of the growth parameters made on both the microalgae showed that divalent nickel retarded the growth of algae at the higher concentration used even though low test concentrations had a stimulatory effect. It was found that nickel toxicity is related to the presence of divalent nickel and can be influenced by environmental factors.